Extraction of Polyphenols in Green Tea Shoots as Antioxidant Substance - Siskayanti, Rini; Rizkiah, Riza; Muliati, Lia; Nurilah, Andini; Subagja, Deden; Fadil, MI (Universitas Insan Cendekia Mandiri, 2024)
Green tea is a plant that has polyphenolic active compounds. Polyphenols are a group of compounds that act as natural antioxidants. Antioxidants are needed by the body to protect the body from free radical attacks. The polyphenol content in the tea leaves itself is influenced by the weather, variety, soil type, and the degree of maturity of the leaves when picked. Therefore, in this study green tea shoots were used because the polyphenol content and antioxidant activity of green tea in the shoots are known to be greater than the leaves on the stalks below. This study aims to determine the levels of polyphenols in green tea shoots using distilled water, 50% ethanol; 96% ethanol and determine the value of antioxidant activity obtained from the results of samples that have the highest levels of total polyphenols by maceration method for 24 hours. The results of maceration are then separated between the filtrate and the precipitate. Then the filtrate is concentrated to obtain a thick extract and removes the remaining solvent using a rotary evaporator that is set to a pressure of 1 bar and a temperature below the boiling point of the solvent. Furthermore, the viscous extract obtained was tested by the Follin-Ciocalteu method using UV-Vis spectrophotometry at a wavelength of 765 nm and gallic acid as a standard to determine the levels of polyphenolic compounds. The test results for the highest levels of polyphenols were tested for antioxidant activity using the DPPH method (2,2 Diphenyl -1-Pikrylhidrazyl) which causes a color change and then measured using a spectrophotometer at a wavelength of 512 nm. Antioxidant activity can be seen from the IC50 (inhibitory concentration) value or the concentration that can reduce 50% of free radicals because the lower the IC50 value, the greater the antioxidant activity. The results showed that the levels of polyphenols in green tea shoot extract were respectively 16.47%; 22.16%; 18.09% so that the highest levels of polyphenols were obtained in green tea leaf extract macerated using 50% ethanol solvent. The results of the antioxidant activity test on samples using 50% ethanol solvent obtained an IC50 value of 5.7 ppm and included in the very good category.